2014
DOI: 10.5486/pmd.2014.5815
|View full text |Cite
|
Sign up to set email alerts
|

On the Diophantine equation (x-1)^k+x^k+(x+1)^k=y^n

Abstract: In this paper, we study the Diophantine equation (x − 1) k + x k + (x + 1) k = y n , n > 1, and completely solve it for k = 2, 3, 4.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
151
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(159 citation statements)
references
References 9 publications
8
151
0
Order By: Relevance
“…11 This genus was first characterized in 2014 following reclassification of members of the genus Thalassomonas. 11 There have been only 10 species of Thalassotalea discussed in the literature and they have been primarily studied for their agarolytic properties, commensalism with marine animals, and pathogenic contribution to coral diseases. 1116 To date, there have been no published secondary metabolite studies on this genus.…”
mentioning
confidence: 99%
“…11 This genus was first characterized in 2014 following reclassification of members of the genus Thalassomonas. 11 There have been only 10 species of Thalassotalea discussed in the literature and they have been primarily studied for their agarolytic properties, commensalism with marine animals, and pathogenic contribution to coral diseases. 1116 To date, there have been no published secondary metabolite studies on this genus.…”
mentioning
confidence: 99%
“…Zhongfeng Zhang [21] showed that the only perfect powers that are sums of three consecutive cubes are precisely those already noted by Euler (1), Lucas (2) and Cassels (3). Zhang's approach is write the problem as (4) y n = (x − 1) 3 + x 3 + (x + 1) 3 = 3x(x 2 + 2), and apply a descent argument that reduces this to certain ternary equations that have already been solved in the literature.…”
Section: Introductionmentioning
confidence: 71%
“…By the conclusion of Lemma 4.1, we know that y 1 , y 2 are integers. It follows from (21) that S | y 1 where…”
Section: Frey-hellegouarch Curve For the Case R = Tmentioning
confidence: 99%
“…They first proved that all integer solutions of equation (1.4) such that n > 1 and d = x are (x, y) = (0, 0), (x, y, n) = (1, ±2, 2), (2, ±5, 2), (24, ±182, 2) or (x, y) = (−1, −1) with 2 ∤ n. Secondly, they showed that if p ≡ ±5 (mod 12) is prime, p | d and v p (d) ≡ 0 (mod n), then equation (1.4) has no integer solution (x, y) with k = 2. In 2014, the equation (x − 1) k + x k + (x + 1) k = y n x, y, n ∈ Z, n ≥ 2, (1.5) was solved completely by Zhang [22], for k = 2, 3, 4 and the next year, Bennett, Patel and Siksek [4], extend Zhang's result, completely solving equation (1.5) in the cases k = 5 and k = 6. In 2016, Bennett, Patel and Siksek [5], considered the equation (1.4).…”
Section: Introductionmentioning
confidence: 99%